The most common strategies and techniques in the writing process applied to composition II courses in the teaching english major at the Foreign Language Department of the school of Arts and Sciences of the University of El Salvador, semester I-2015 - Orellana, Betty Lorena; Navarro Rivera, Patricia Elizabeth; Guzmán, Rolando; Ayala, Edgar Nicolás (San Salvador : Universidad de El Salvador, 2015)
Chapter two, in this chapter there is the theoretical framework, theories from experts on the topic, also authors and theoreticians who had studies and information who help the research group to do the investigation, moreover, there are two important concepts to know. First, it is essential to know what a strategy is, according to the Cambridge Dictionary: strategy is a plan that you use to achieve something. And the second concept to know is technique: a technique is the way in which a (usually skilled) process should be carried out.
Tesis (Licenciada en Lenguas Modernas Especialidad en Francés e Inglés) -- Universidad de El Salvador 2015.
hojas 111-112
Keywords: Inglés -- Enseñanza; Métodos de enseñanza